Exclusive Breastfeeding could Minimize the Incidence of Stunting in Children Aged 2-3 Years in the Community of Rejosari Health Centre in Pekanbaru - Muslim Suardi; Sara Herlina; Yulia Afrina (LPPM Universitas Abdurrab, 2025)
Background: Stunting is a condition of growth failure in infants due to several causes, which can impact both physical and cognitive development. One of the preventive factors for stunting is exclusive breastfeeding. Objective: To determine the relationship between exclusive breastfeeding and the incidence of stunting in infants aged 2–3 years in the service area of the Rejosari Community Health Centre, Pekanbaru. Method: This is a quantitative study with a cross-sectional design. The study was conducted in June-July 2025. The population was children aged of 2-3 years that have experience of stunting, with a sample size of 34 participants using a total sampling technique. The data sources used were primary and secondary data. The instrument used was a microtoise, with the research instrument being a questionnaire on exclusive breastfeeding. Data were analysed based on univariate and bivariate analysis using the Chi-Square test and Mann-Whitney test, with a normality test conducted prior to the Mann-Whitney test. Results: It showed that significant relationship between exclusive breastfeeding and the occurrence of stunting (p = 0.024 OR value of 10.909). Result of the Mann-Whitney test showed a significant difference in TB/U z-scores between toddlers who received exclusive breastfeeding and those who did not (p = 0.003). Conclusion: There is a significant relationship between exclusive breastfeeding and the occurrence and severity of stunting in toddlers aged of 2–3 years. Toddlers who are not exclusively breastfed have a higher risk of stunting. Efforts are needed to raise mothers' awareness of the importance of exclusive breastfeeding in preventing stunting.